Pengaruh Budaya dan Tunjangan Terhadap Kinerja Pegawai Pada Bagian Protokol Kabupaten Lampung Selatan - Agustuti Handayani; Rizky Zul Indrawan (e-JKPP, 2023)
The problems of this study were: (1) Does organisational culture affect the performance of the employees in the Protocol Section of the South Lampung Regency Secretariat. (2) Does performance reward affect employee performance in the Protocol Section of South Lampung Regency Secretariat. (3) Does organisational culture and performance reward together affect employee performance in South Lampung Regency Secretariat Protocol Section. The study uses quantitative techniques aimed at discovering the influence of independent and dependent variables and testing the significance of the influence among these variables. In this way, the extent of influence of independent variables on dependent variable is known. The survey technique is used to take samples from the population. Samples are taken that are representative. They are analysed to draw conclusions that can then be generalised to the population. The results show that (1) some organisational culture variables have a positive and significant effect on employee performance. The more conducive (good) organisational culture, the more the performance of employees in the Regional Secretariat Protocol Section South Lampung Regency will improve. (2) The performance allowance variable has a positive and significant effect on the performance of the RSO. This shows that the better performance allowance in this case, providing compensation and commissions will further improve performance of employees in Regional Secretariat Protocol Section South Lampung Regency. (3) It is also found that organisational culture and performance bonus combine to produce a positive and significant effect on performance.